English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

X=Y
X^2=XY
Y^2=XY
(X+Y)(X-Y)= Y(X-Y)
devide by (X-Y)
X+Y=Y
if X=1
then Y=1
so 1+1=1?

2007-01-11 04:50:04 · 20 answers · asked by trevelan7 2 in Science & Mathematics Mathematics

20 answers

you divide by X-Y, but X-Y =0 and you cant divide by 0 in maths-its not defined (not allowed basically!)

2007-01-11 04:53:43 · answer #1 · answered by impeachrob 3 · 2 1

Where did i go wrong?
X=Y
X^2=XY
Y^2=XY
(X+Y)(X-Y)= Y(X-Y)
devide by (X-Y) ....YOU MISSPELLED DIVIDE That's where you went wrong.
X+Y=Y
if X=1
then Y=1
so 1+1=1?

2007-01-11 12:57:25 · answer #2 · answered by Keith W 2 · 0 1

step 3 to 4

2007-01-11 13:00:52 · answer #3 · answered by CAM1122 3 · 0 1

In step 5 you divided by x-y which is 0
Division by zero is not permitted.
This is such a well known puzzle that I am surprized it still makes the rounds.

2007-01-11 13:08:04 · answer #4 · answered by ironduke8159 7 · 1 0

well...put in 1 at the 3rd line...you have (2)(0)=1(0)
so 0=0... you really cant continue, and if you say, yeah but we are gonna divide by x-y to get rid of that issue, now your dividing by zero...and you cant do that

hope that helped
matttlocke

2007-01-11 12:55:10 · answer #5 · answered by matttlocke 4 · 1 1

I think this will only work for X=0 & Y=0, but I'm not that good in math, maybe I'm overlooking something!

2007-01-11 12:56:08 · answer #6 · answered by Sheriam 7 · 0 1

(X+Y)(X-Y)= Y(X-Y)
this implies that Y = X+Y, and that can only be true if X and Y both equal 0

also, If X = Y, then X-Y= 0

So this statement comes out to be 0=0

plus you can't divide by (X-Y) because that is dividing by 0

2007-01-11 12:56:07 · answer #7 · answered by Anonymous · 0 1

Line five (divide by (X-Y)) is invalid because X-Y=0.

You cannot divide by zero.

2007-01-11 12:56:32 · answer #8 · answered by Dendryte88 4 · 1 0

The fourth line doesn't equal to the previous line. It is wrong.
(X+Y)(X-Y)= Y(X-Y)

equals

x^2-y^2 = xy-y^2

add y^2

x^2 = xy is wrong.

2007-01-11 12:56:10 · answer #9 · answered by Wocka wocka 6 · 0 2

if x = y , then x^2 = y^2 ... no ?
unless, and only unless the book statest that Y^2=XY and X^2=XY
Anyways!
(X+Y)(X-Y)= X (Y-Y) NOT Y(X-Y)

2007-01-11 12:55:59 · answer #10 · answered by Anonymous · 0 1

fedest.com, questions and answers